Foundations of kinesiology : a modern integrated approach - Tinker Dan Murray; James Eldridge; Harold W. Kohl (Boston, Massachusetts : Cengage, 2019)
Teaches undergraduates to incorporate evidence-based practice strategies as they prepare for specific Kinesiology careers. Combining digital and traditional delivery methods, the authors provide a solid foundation in basic Kinesiology and subdisciplines such as biomechanics, motor learning, exercise physiology and public health. They also emphasize skills needed for effective careers in personal training, occupational and physical therapy, athletic training, sports psychology and sports management. A running case requires students to create solutions that promote physically active lifestyles for various circumstances. MindTap Health propels students from memorization to mastery with numerous digital learning tools including Career Insights Videos
Keywords: Applied kinesiology; Kinesiology Textbooks